THE ENHANCEMENT OF BATIK CULTURAL LITERACY (SHIBOTIK) WITH STUDENTS OF FISIP PASUNDAN UNIVERSITY - Imam Budiman; Bulbul Badurrachman; Gusti Salma Masmulia Rahmah; Kiki Safitri (LPM Universitas Pasundan, 2023)
Batik regeneration is an alternative to preserving batik as an asset for Indonesia. Shibotik is one of the SMEs batik craftsmen that provide new innovations in the manufacturing process, by collaborating on the Shibori coloring technique from Japan. The products that they sell are very suitable for the young generation, either in terms of models, colors, and patterns. However, the achievement of the target for young generations is still not optimal because the level of sales is still directed at adulthood, especially for women. Based on the analysis conducted by our research team, the younger generation chooses to buy batik that has low prices regardless of the process of making batik which loses the essence of making batik itself. So that, our team is trying to provide a solution in the form of technical guidance in the procurement of focus group discussions with the target of FISIP UNPAS student participants who have interest and activity in certain fields. Through this FGD, Shibotik owners can become a speaker to growing batik literacy and awareness of FISIP UNPAS students in batik discovery, entrepreneurship, and introduce Shibotik as a new innovation in batik. In addition, students can provide suggestions according to their respective focus on the problems faced so that Shibotik can more optimally reach its main target market, which is the younger generation.